Scenario Planning Of Halal Tourism Development (Study in West Lombok Regency, West Nusa Tenggara Province) - Vidya Yanti Utami (Jurnal Administrasi Publik, 2017)
Halal tourism is a new tourism concept applied by the West Lombok Regency to provide products, services and management of tourism that meet the values of Islam/Sharia. However, the development of halal tourism in West Lombok Regency still  not optimal because stakeholders are still not cooperating well, so it takes good planning to analyse and provide an overview (scenario) condition of halal tourism in the future. The method used to compile the scenario planning in this research is a method of T-A-I-D. It produces a scenario planning ranging from best to worst in halal tourism development and its impact on PEST aspects that is Politic, Economic, Social and Technology. This research is expected to provide an overview of the development of halal tourism in West Lombok Regency and minimize the impacts and effects that may arise from the development of halal tourism and to sharpen a strategy.